The Mongolian Gerbil as a Useful Experimental Model in Reproductive Biology - Ruiz, Thalles Fernando Rocha [UNESP]; Vilamaior, Patricia Simone Leite [UNESP]; Grigio, Vitor [UNESP]; Colleta, Simone Jacovaci [UNESP]; Zucão, Mariele Ilario [UNESP]; de Campos, Silvana Gisele Pegorin [UNESP]; dos Santos, Fernanda Cristina Alcântara; Biancardi, Manoel Francisco; Perez, Ana Paula Silva; Taboga, Sebastião Roberto [UNESP]; Leonel, Ellen Cristina Rivas (Springer Nature, 2023)
Ultimately, the Mongolian gerbils (Meriones unguiculatus) have acquired a relevant role in biological and biomedical experiments alongside other rodents. The use of gerbils in research has been mainly oriented to physiological and pharmacological studies, with special attention to nervous, digestive, and auditory systems as well as microbiology and parasitology. Ultimately, gerbils have also been applied for studying carcinogenesis in different organs and systems, since these animals show a natural propensity to develop spontaneous proliferative lesions, especially in steroid-responsive organs. This characteristic shed light on the reproductive aspects of this rodent model regarding morphological features in male and female individuals. This review of literature summarizes the significance of this model as an alternative to the use of inbred mice and rats in reproductive experimental research, highlighting recent findings. Gerbils have contributed to the expansion of knowledge in prostate biology in male and female individuals, providing studies related to prostatic morphogenesis and neoplasia. In the testes, spermiogenesis occurs in 15 steps, differently from other experimental models. Also, the complete maturation of the testis-epididymal complex occurs between the second and third months. Mammary gland alterations related to the estrous cycle and pregnancy were described, as well as its modulation under endogenous and exogenous estrogenic compounds. The ovaries frequently present ovarian cysts. Furthermore, this organ shows predominantly interstitial steroidogenic glands in the stroma, especially at aging. Adrenal gland shows a large size compared to other animals, presenting three distinct zones with a remarkable role in steroidogenesis.
Keywords: Animal experimentation; Morphology; Reproduction; Rodent